Biochemical markers of cartilage metabolism are associated with walking biomechanics 6‐months following anterior cruciate ligament reconstruction. Issue 10 (2nd March 2017) - Pietrosimone, Brian; Loeser, Richard F.; Blackburn, J. Troy; Padua, Darin A.; Harkey, Matthew S.; Stanley, Laura E.; Luc‐Harkey, Brittney A.; Ulici, Veronica; Marshall, Stephen W.; Jordan, Joanne M.; Spang, Jeffery T.
ABSTRACT: The purpose of our study was to determine the association between biomechanical outcomes of walking gait (peak vertical ground reaction force [vGRF], vGRF loading rate [vGRF‐LR], and knee adduction moment [KAM]) 6 months following anterior cruciate ligament reconstruction (ACLR) and biochemical markers of serum type‐II collagen turnover (collagen type‐II cleavage product to collagen type‐II C‐propeptide [C2C:CPII]), plasma degenerative enzymes (matrix metalloproteinase‐3 [MMP‐3]), and a pro‐inflammatory cytokine (interleukin‐6 [IL‐6]). Biochemical markers were evaluated within the first 2 weeks (6.5 ± 3.8 days) following ACL injury and again 6 months following ACLR in eighteen participants. All peak biomechanical outcomes were extracted from the first 50% of the stance phase of walking gait during a 6‐month follow‐up exam. Limb symmetry indices (LSI) were used to normalize the biomechanical outcomes in the ACLR limb to that of the contralateral limb (ACLR/contralateral). Bivariate correlations were used to assess associations between biomechanical and biochemical outcomes. Greater plasma MMP‐3 concentrations after ACL injury and at the 6‐month follow‐up exam were associated with lesser KAM LSI. Lesser KAM was associated with greater plasma IL‐6 at the 6‐month follow‐up exam. Similarly, lesser vGRF‐LR LSI was associated with greater plasma MMP‐3 concentrations at the 6‐month follow‐up exam. Lesser peak vGRF LSI was associated with higher C2C:CPII after ACL injury, yet this association was not significant after accounting for walking speed. Therefore, lesser biomechanical loading in the ACLR limb, compared to the contralateral limb, 6 months following ACLR may be related to deleterious joint tissue metabolism that could influence future cartilage breakdown. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2288–2297, 2017.